2006
DOI: 10.2320/matertrans.47.2292
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Time-Resolved X-ray Diffraction Study of Directional Solidification in Steels

Abstract: In situ characterization of directional solidification process during welding was carried out using the time resolved X-ray diffraction technique utilizing intense synchrotron radiation. Then, behaviour of dendrites in steels under welding conditions of a practical manufacturing process were investigated using the TRXRD method for in-situ weld observation with the uniquely-sensitive two-dimensional pixel detector. Consequently, the crystal growth during the rapid cooling was caught in detail and employed a sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 23 publications
0
37
0
Order By: Relevance
“…The rapid cooling is a result of the heat absorption by the cold steel adjoining the molten weld leading to rates as high as several hundred C s À1 . 14) The experimental observations of Yonemura et al provided in situ diffraction patterns of the phase transformation process during rapid weld cooling. The experimental procedure was possible because of the availability of intense X-ray beams from synchrotron storage rings.…”
Section: Results Of Quenching Studies On 088 Mass% C Steelmentioning
confidence: 99%
See 2 more Smart Citations
“…The rapid cooling is a result of the heat absorption by the cold steel adjoining the molten weld leading to rates as high as several hundred C s À1 . 14) The experimental observations of Yonemura et al provided in situ diffraction patterns of the phase transformation process during rapid weld cooling. The experimental procedure was possible because of the availability of intense X-ray beams from synchrotron storage rings.…”
Section: Results Of Quenching Studies On 088 Mass% C Steelmentioning
confidence: 99%
“…Yonemura et al 14,15) have studied changes in the structure of Fe-C steels as they solidify from the molten state during welding. Their work involves in situ measurements taken using a time-resolved, X-ray diffraction technique as pioneered by Babu et al 16,17) and Elmer et al 18) The uniqueness and value of the Yonemura et al study is the use of a very fast detector with very fine time resolution for capturing individual diffraction peaks during quenching.…”
Section: Results Of Quenching Studies On 088 Mass% C Steelmentioning
confidence: 99%
See 1 more Smart Citation
“…Succinonitrile solidifies at about 329K, which simplifies the study of solidification phenomena, but the question remains as to what extend such solidification studies replicate the solidification behaviour of steel. Sen et al (1997) and more recently Yonemura et al (2006) suggested the use of X-ray transmission microscopy to study the solid/liquid interface during the solidification of metals, but they were unable to observe the evolution of the interface.…”
Section: Introductionmentioning
confidence: 99%
“…1,2) In general, the final microstructures of the casting are the result of the competition between the growth of an outer columnar (oriented properties) and an inner equiaxed (isotropic properties) grains. 3) Traditionally, most previous studies of the microstructure have relied on the post-solidification, optically transparent materials and computer simulation.…”
Section: Introductionmentioning
confidence: 99%